Quarks and Letters. Natural Sciences in Contemporary Literature and Culture - v. Heydenreich, Aura (Literatur- und Naturwissenschaften, 2015)
Issues and insights from the fields of brain research, quantum mechanics, and evolutionary theory have passed into novels, and physicists and biologists often use rhetorical metaphors to communicate and even evoke their discoveries. The essays in this volume examine natural scientific themes in literary texts - such as the novels of Richard Powers, Can Hue, and Raoul Schrott - and the use of rhetoric and metaphor in the natural sciences.